Translation Practices in Indonesian Senior High Schools: A Literature Review Based on Suryawinata and Hariyanto’s Perspectives - Ikrimah, Ikrimah; Fauzan, Akhmad (EDUPEDIA Publisher, 2025)
This study aims to explore the relevance and pedagogical implications of Suryawinata and Hariyanto’s translation theory in Indonesian senior high school contexts. Translation is recognized not only as a linguistic skill but also as a tool to develop students’ cultural understanding and critical thinking in English language education. Employing a qualitative descriptive design in the form of a literature review, the study analyzed 46 sources, including books, journal articles, and conference proceedings, published between 2009 and 2025 in both Indonesian and English. These sources were selected based on their relevance to translation pedagogy, strategies, and classroom practices. The findings indicate that the structured stages of the Suryawinata and Hariyanto model (analysis, transfer, restructuring, and evaluation) align well with the needs of Indonesian high school students and can support curriculum goals by promoting linguistic accuracy and cultural sensitivity. Despite challenges such as limited class time, varying student proficiency levels, and lack of specialized teaching materials, the model offers opportunities for integration into project-based learning, formative assessment, and cross-curricular instruction. The novelty of this study lies in its systematic synthesis of translation theory and its practical connection to secondary education, an area that has been underexplored in previous research. This review provides a foundation for future instructional innovation and material development, particularly for teachers, curriculum designers, and educational researchers seeking to enhance English language learning through translation.